A sibling study of whether maternal exposure to different types of natural space is related to birthweight. (13th December 2017) - Richardson, Elizabeth A; Shortt, Niamh K; Mitchell, Richard; Pearce, Jamie
Abstract: Background: Birthweight is an important determinant of health across the life course. Maternal exposure to natural space has been linked to higher birthweight, but stronger evidence of a causal link is needed. We use a quasi-experimental sibling study design to investigate if change in the mother's exposure to natural space between births was related to birthweight, in urban Scotland. Methods: Amount (% area) of total natural space, total accessible (public) natural space, parks, woodlands and open water within 100 m of the mother's postcode was calculated for eligible births ( n = 40 194; 1991–2010) in the Scottish Longitudinal Study (a semi-random 5.3% sample of the Scottish population). Associations between natural space and birthweight were estimated, using ordinary least squares and fixed effects models. Results: Birthweight was associated with the total amount of natural space around the mother's home (+8.2 g for interquartile range increase), but was unrelated to specific types of natural space. This whole-sample relationship disappeared in the sibling analysis, indicating residual confounding. The sibling models showed effects for total natural space with births to women who already had children (+20.1 g), and to those with an intermediate level of education (+14.1 g). Conclusions: The importance of total natural space for birthweight suggests that benefits can be experienced near to as well as within natural space. Ensuring expectant mothers have good access to high quality neighbourhood natural space has the potential to improve the infant's start in life, and consequently their health trajectory over the life course.